Analisis Lingkungan Kerja Dalam Meningkatkan Kinerja Pegawai Pada Kantor Kelurahan Jurang Mangu Barat Kota Tangerang Selatan - Rahmawati Rahmawati; Dewi Lestari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the role of the work environment in improving employee performance at the Jurang Mangu Barat Village Office. The work environment is an important factor that influences the implementation of employee duties, both related to physical and non-physical conditions, thus impacting the effectiveness and quality of performance. The physical work environment includes the availability of facilities, infrastructure, and workspace layout, while the non-physical work environment includes interpersonal relationships, communication, work atmosphere, and leadership support. These two aspects are interrelated in creating conducive and productive work conditions. This study aims to analyze the role of the work environment in improving employee performance at the Jurang Mangu Barat Village Office. The work environment is an important factor that influences the implementation of employee duties, both related to physical and non-physical conditions, thus impacting the effectiveness and quality of performance. The physical work environment includes the availability of facilities, infrastructure, and workspace layout, while the non-physical work environment includes interpersonal relationships, communication, work atmosphere, and leadership support. These two aspects are interrelated in creating conducive and productive work conditions.